Lost virtue professional character development in medical education - Kenny, Nuala P.; Shelton, Wayne N. (Elsevier, 2006)
Discusses character formation, ethics, professional character, and other concepts and addresses the interpersonal aspects of physicians as well as the importance of character.
Keywords: Medical ethics.; Medical ethics -- Study and teaching.; Moral education (Higher); Medical ethics & professional conduct.; Medical -- Education & Training.; Medical -- Ethics.; elektronické knihy; electronic books